Compatibility of Elastomers in Biodiesel-diesel-bioethanol Blend (BDE) - Thangavelu, S.K.; Piraiarasi, C.; Abu Saleh, Ahmed; Ani, F.N. (Trans Tech Publications, 2015)
The present study aims to investigate the impact of biodiesel-diesel-bioethanol (BDE) blended fuel on the degradation behavior of elastomers such as nitrile rubber (NBR) and polytetrafluroethylene (PTFE). Static immersion test in B20D75E5 blends (20% biodiesel, 75% diesel and 5% bioethanol) at 50°C for 200 h was carried out. At the end of immersion test, degradation behaviour of elastomers was investigated by measuring mass, volume and hardness. The exposed surface of elastomers was studied using optical microscope (OM). Fourier Transform Infrared (FTIR) spectroscopy was carried out to identify the chemical and structural changes in the elastomers. Moreover, physical and chemical characteristics of the fuel blend after the immersion test such as total acid number (TAN), density and colour change were also investigated. Results showed that the degradation of NBR was high compared to PTFE.